Moldova : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper describes economic developments in the Republic of Moldova during the 1990s. In February 1993, the Executive Board of the IMF approved a purchase of resources equivalent to SDR 13.5 million under the compensatory and contingency financing facility to cover the costs associated with the need to import grains because of the drought and subsequent crop failure in Moldova. A World Bank Emergency Drought Recovery Project in an amount equivalent to USD 26 million was also approved in February 1993.